2022
DOI: 10.1111/tops.12608
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the Goal: Superior Navigators in Late Adulthood Provide a Novel Perspective into Successful Cognitive Aging

Abstract: Normal aging is typically associated with declines in navigation and spatial memory abilities. However, increased interindividual variability in performance across various navigation/spatial memory tasks is also evident with advancing age. In this review paper, we shed the spotlight on those older individuals who exhibit exceptional, sometimes even youth‐like navigational/spatial memory abilities. Importantly, we (1) showcase observations from existing studies that demonstrate superior navigation/spatial memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 169 publications
0
6
0
Order By: Relevance
“…Despite these neural challenges, some older adults appear to maintain cognitive abilities as they age, showing relatively lesser decline as compared to others in their age cohort. These individuals, or 'super-agers', who can achieve successful cognitive aging trajectories through the maintenance of one's cognition and flexibility (i.e., 'optimal aging'), experience less pathological atrophy in their brains (Borelli et al, 2018;Zhou et al, 2023) and show maintenance of neurotransmitter systems (e.g., dopamine) (Ciampa et al, 2022;Nordin et al, 2022;Rieckmann et al, 2011). This attests to the efficacy of neuroplasticity, even in old age, where the organization of the brain can still change substantially as a result of continuous practice and experience in enriched sensory environments, such as active engagement with music (Shaffer, 2016).…”
Section: Age-related Changes In Hierarchy and Uncertainty Estimatementioning
confidence: 99%
“…Despite these neural challenges, some older adults appear to maintain cognitive abilities as they age, showing relatively lesser decline as compared to others in their age cohort. These individuals, or 'super-agers', who can achieve successful cognitive aging trajectories through the maintenance of one's cognition and flexibility (i.e., 'optimal aging'), experience less pathological atrophy in their brains (Borelli et al, 2018;Zhou et al, 2023) and show maintenance of neurotransmitter systems (e.g., dopamine) (Ciampa et al, 2022;Nordin et al, 2022;Rieckmann et al, 2011). This attests to the efficacy of neuroplasticity, even in old age, where the organization of the brain can still change substantially as a result of continuous practice and experience in enriched sensory environments, such as active engagement with music (Shaffer, 2016).…”
Section: Age-related Changes In Hierarchy and Uncertainty Estimatementioning
confidence: 99%
“…The use of virtual environments has enabled extensive study of differences in navigational processes associated with older age (Diersch & Wolbers, 2019;Wiener et al, 2020). Generally, healthy aging is associated with a decline in spatial navigation abilities (but see Zhou et al, 2022 for a review of superior older navigators), and problems with navigation are often the first behavioral signs of Alzheimer's dementia. A number of the VR tasks (or variations of them) described in this section have been used to help to identify changes in cue use, strategies, and spatial learning that occur with aging, both with behavioral and neural measures.…”
Section: Age Differencesmentioning
confidence: 99%
“…The relationship between spatial memory performance and hippocampus subfield MPS, however, remains untested in older adults. Because older adults show individual differences in spatial memory with aging (15,16), one possibility is that agerelated differences in remapping may instead relate to poorer spatial memory, regardless of the age of the individual ("age-invariant"). For example, Schimanski et al (2013) found that both older and younger rats with lower correlations in place cell representations in CA1 within the same environment also showed worse performance on the Morris watermaze (6).…”
Section: Main Text Introductionmentioning
confidence: 99%